S99 Lung cancer surgical outcomes in england (2015). (15th November 2017) - Beckett, P; Dickinson, R; Hubbard, R; Khakwani, A; West, D
Abstract : Introduction: The National Lung Cancer Audit has collected data for over 10 years demonstrating gradually rising resection rates in the UK. The Clinical Outcomes Programme (COP) uses national audit data to publish quality measures at the level of individual consultants. The lung cancer COP focusses on activity at individual surgeon level, and on survival at unit level. Previous rounds of this audit demonstrated overall 30 and 90 day survival of 97.8% and 95.5% (2013) and 97.9% and 96.2% (2014). Methods: Data submitted to the NLCA for patients having curative-intent surgery who underwent surgery in 2015 was sent to the clinical lead at each surgical unit for validation and addition of responsible surgeon GMC number, with the option to add surgical cases if they were not included in the supplied dataset. Date of death was derived by a link to the Office of National Statistics. Units reporting unadjusted survival proportions more than three standard errors outside the national mean ("alarm" level) at 30 or 90 days were identified as statistical outliers. Results: All of the 28 surgical units in England participated in the audit, submitting a total of 5843 cases, of which 93% were NSCLC, 2% SCLC and 6% carcinoid. Median annual unit activity was 186 resections (IQR 141–264, range 49–507), an increase over the median 156 in the previous year. Median annual activity for individual surgeons was 44 (IQR 18–67, range 1–171). Median LOS 8.1 days (median 6, IQR 4–9). Overall 30 day survival was 98.2% and 90 day survival was 96.3%. There were no units with statistical outliers at the alarm level at 30 days and 90 days (see figure 1 ). Overall 1 year survival 87.9%. Conclusion: Volume of activity varies widely by unit and individual surgeon. Survival after lung cancer surgery is very high, is improving, and is not statistically significantly different across the surgical units in England. New measures are needed to properly reflect features that are important to patients.